Travmatska luksacija kolka pri otroku - Ovnič, Stanislav (Zdravniški vestnik, 2006)
Background A traumatic dislocation of the hip joint of children is a rare injury. There is a considerable difference between dislocation of the hip in children under 5 year of age, where a trivial trauma is enough to produce dislocation of the hip and the adolescents, where traffic accident is a cause usual for dislocation. A prompt reduction of the hip is indicated. A successful reposition has to be confirmed by an x-ray, with the clear evidenceof the femoral head lying concentrically in the acetabulum. A poorer prognosis is asociated with delay in reduction beyond 6 hours. The reduction is usually easy to achieve, but labral, capsular or osteochondral fragment interposition may prevent concentric reduction and thus requires surgery to achieve anatomic reduction. A vascular necrosis of the femoral head and posttraumatic arthritis are most common long term complications. The postreduction treatment remains without particular consensus. Conclusions We are going to present an example of a three year-old girl in whose posterior dislocation of the hip occured after some trivial trauma. She was treated conservatively with closed reduction and later with limited weight bearing.
Keywords: child; Child, Preschool; Femur Head Necrosis; Femur, glavica, nekroza; Hip Dislocation; izpah kolka; kolčni sklep; Kolk, dislokacija; otroci; Otrok predšolski; poškodbe; Rane in poškodbe; therapy; Wounds And Injuries; zdravljenje